2020
DOI: 10.1542/peds.2019-3307
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Readiness in Emergency Medical Services Systems

Abstract: on pediatric readiness in emergency medical services systems. Prehospital emergency care typically involves emergency medical technicians, paramedics, and other licensed medical providers who work in emergency medical services (EMS) systems in ground ambulances and fixedor rotor-wing aircraft that are dispatched to an emergency when either a bystander calls 9-1-1 or when a patient requires interfacility transport for a medical illness or traumatic injury. Because prehospital emergency care of children plays a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…This dilution of exposure translates to the need for reiterative and robust training, quality improvement, education, and skills courses to maintain PR. Recognizing the importance of the topic but the constraints of daily clinical care, the American Academy of Pediatrics, American College of Emergency Physicians, Emergency Nurses Association, National Association of EMS Physicians, and National Association of Emergency Medical Technicians (EMT) released a joint policy statement on PR in EMS systems in 2019 29–31 . The purpose was to highlight the need for uniform pediatric prehospital care and to recommend standards based on PR needs in trauma care 32 .…”
Section: Pr In Ems Systemsmentioning
confidence: 99%
“…This dilution of exposure translates to the need for reiterative and robust training, quality improvement, education, and skills courses to maintain PR. Recognizing the importance of the topic but the constraints of daily clinical care, the American Academy of Pediatrics, American College of Emergency Physicians, Emergency Nurses Association, National Association of EMS Physicians, and National Association of Emergency Medical Technicians (EMT) released a joint policy statement on PR in EMS systems in 2019 29–31 . The purpose was to highlight the need for uniform pediatric prehospital care and to recommend standards based on PR needs in trauma care 32 .…”
Section: Pr In Ems Systemsmentioning
confidence: 99%
“…Given the lack of demographics or further information from non-responders, it is difficult to make any conclusions. 13,15…”
Section: Limitationsmentioning
confidence: 99%
“…The reported proportion of EMS contacts in pediatric patients varies between 4% in Finland [1], 5% in Canada [2] and 7% in Denmark, Korea and United States [3][4][5]. However, children have unique needs in a healthcare setting and EMS has to address these needs [6]. The Academic Emergency Medicine Consensus Conference on "Aligning the Pediatric Emergency Medicine Research Agenda to Reduce Health Outcome Gaps" identified organization and administration of pediatric EMS as one of high-priority research issues [7].…”
Section: Introductionmentioning
confidence: 99%